Inducting Students into Professional Discourse: A Corpus-Based Study in English for Islamic Studies - Asmiyah, Siti (Universitas Islam Negeri Sunan Ampel Surabaya, 2025)
In the context of teaching English for Islamic studies, English for Specific Purposes (ESP) is the prevalent approach. Students’ needs for their preparation toward their professional practice are central considerations in ESP. Understanding professional practices is, therefore, inevitable. Corpora of academic sources in the discipline can serve as a firm reference for English for Islamic studies. This study explored corpora of English article abstracts from the international journal of Islamic studies and from reference books on English for Islamic studies. The abstracts were collected from international journals in Islamic studies, while the books served as references at three universities in Indonesia. The corpora were analyzed using AntConc. The study further compares the existing corpora from the two sources and evaluates their conformity. The study examines the extent of conformity regarding the adequacy of reference books in preparing students for future professional discourse. The findings of this study are significant not only as a reflection on current practice in English for Islamic studies in the context of Indonesian ESP, but also as a foundation for further improving the course’s teaching to better cater to students’ needs.